Turnover Intention: Introduction, Types, Causes, and Measurements (A Review) - Hugo Fostin Hokianto (Asosiasi Fakultas Ekonomi dan Bisnis Indonesia, 2023)
Turnover has been a recurring phenomenon for companies and businesses to face. The shift in employees that are constantly changing causes them to either stay, or leave, whether voluntarily or forcefully. The focus on companies then emphasizes on reducing turnover as low as possible. But what creates turnover in the first place? This paper reviews Turnover, by explaining definition, types, causes, and measurements that are related to turnover, especially turnover intention, as it’s the best predictor to determine whether an employee will stay or leave. The research is qualitative, using literature review as the research method, results in a comprehensive explanation of turnover definition, the types of turnover according to literatures, the cause of turnover that happened in the workforce, and what measurements are used to determine a turnover, which includes measurements of turnover rate to analyze employees that are leaving in a time period, and turnover intention to survey whether an employee feels the need to leave.